Combination of aztreonam, ceftazidime–avibactam and amikacin in the treatment of VIM-1 Pseudomonas aeruginosa ST235 osteomyelitis. (July 2021) - Mularoni, Alessandra; Mezzatesta, Maria Lina; Pilato, Michele; Medaglia, Alice Annalisa; Cervo, Adriana; Bongiorno, Dafne; Aprile, Ausilia; Luca, Angelo; Stefani, Stefania; Grossi, Paolo
Highlights: Metallo-beta-lactamase-producing Pseudomonas aeruginosa osteomyelitis is hard to treat. Aztreonam/ceftazidime–avibactam combined with amikacin was strongly synergic. Time-kill curves showed that triple combination achieved 99.9% killing until 48 h. Antipseudomonal synergistic agents plus debridement resolved the infection. Abstract: We describe a challenging case of patient with metallo-beta-lactamase-producing Pseudomonas aeruginosa sternal osteomyelitis following aortic valve replacement with biological prosthesis. The strain exhibited a multidrug-resistance phenotype carrying the bla VIM-1 gene and belonged to the high-risk clone sequence type ST235. The patient was successfully treated with surgical debridement plus antibiotic therapy with ceftazidime/avibactam, aztreonam, and amikacin. Time-kill curves showed that this triple antibiotic combination at 1 × MIC was strongly synergic after 8 h, achieving 99.9% killing and maintaining this until 48 h.